Frequency of Bioprosthetic Valve Fracturing Utilization in an All-Comers Valve-in-Valve TAVR Cohort - Ruge, Hendrik; Erlebach, Magdalena; Lange, Ruediger (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Valve-in-valve TAVR (ViV-TAVR) is an established treatment for failing surgical aortic valves in patient at high surgical risk. Elevated transprosthetic gradients are common after ViV-TAVR. Previously, bench tests showed feasibility of bioprosthetic valve fracturing (VF) using high-pressure balloons. Small case series show reduced transprosthetic gradients using VF. We present our clinical experience and outcome of VF. Material and Methods: Consecutive ViV-TAVR patients were identified from our institutional TAVR database and utilization of bioprosthetic valve fracturing or intraprocedural postdilatation was reviewed. Surgical valves were categorized as responsive or not responsive to VF. Transprosthetic gradients were compared in procedures with VF and procedures with or without postdilatation. Results: In 67 consecutive ViV-TAVR procedures between January 2018 and September 2020, VF was attempted in 15 cases with eight being successful. Standard postdilatation was performed in 21 patients and 31 cases were without postdilatation. Mean transprosthetic gradients (MPG) decreased from 34.2 + 12.5 to 12.7 + 7.4 mmHg (p < 0.001) for all patients. MPG was 8.6 + 3.5 mmHg after VF, 12.9 + 8.5 mmHg after standard postdilatation (p = 0.18) and 13.4 + 6.8 mmHg in cases without postdilatation (p = 0.04). In small surgical valves with true inner diameter <21 mm MPG was 9.1 + 3.5 mmHg after VF, 14.2 + 8.9 after standard postdilatation (p = 0.068) and 16.2 + 9.2 mmHg without postdilatation (p = 0.152). Failed attempts with BVF occurred with the Perimount standard valve. Conclusion: Bioprosthetic valve fracturing results in lower mean transprosthetic gradients after ViV-TAVR. Responsiveness of BVF in Perimount surgical valves, long-term hemodynamic outcome, and potential survival benefits need further evaluation.